Impact of Preoperative Type 2 Diabetes Mellitus on the Outcomes of Gastric Cancer Patients Following Gastrectomy: A Propensity Score Matching Analysis - Cheng, Yu-Xi; Tao, Wei; Kang, Bing; Liu, Xiao-Yu; Yuan, Chao; Zhang, Bin; Peng, Dong (Frontiers in Surgery, 2022)
Purpose The current study aims to explore the outcomes of type 2 diabetes mellitus (T2DM) on gastric cancer patients following gastrectomy through propensity score matching (PSM) analysis. Methods A retrospective study of gastric cancer patients following gastrectomy was conducted in a single clinical center from January 2014 to December 2019. The short-term outcomes, overall survival (OS) and disease-free survival (DFS) were analyzed between T2DM group and Non-T2DM group. Results A total of 703 patients were enrolled in this study. After 1:1 PSM, 84 patients in T2DM group and 84 patients in Non-T2DM were matched for final analysis. No significant difference was found in terms of operation time, intra-operative blood loss, retrieved lymph nodes, postoperative stay, blood transfusion and complications between T2DM group and Non-T2DM group (p>0.05). The Kaplan-Meier curve implied that T2DM had no impact on OS or DFS. Cox regression was conducted to identify predictive factors for prognosis. Body mass index (BMI) (p=0.039<0.05, HR=0.725, 95% CI=0.534-0.983), pre-operative lymphocyte (p=0.017<0.05, HR=0.678, 95% CI=0.493-0.932), pathological tumor node metastasis (pTNM) stage (p=0.000<0.05, HR=2.619, 95% CI=2.048-3.349) and complications (p=0.006<0.05, HR=1.528, 95% CI=1.132-2.061) were predictive factors for OS, and BMI (p=0.013<0.05, HR=0.524, 95% CI=0.315-0.872), pTNM stage (p=0.000<0.05, HR=2.619, 95% CI=2.048-3.349) and complications (p=0.008<0.05, HR=1.892, 95% CI=1.179-3.036) were independent predictive factors for DFS. Conclusion T2DM did not have an impact on gastric cancer patients following gastrectomy in terms of short-term outcomes and prognosis.